Sagot :
Answer:
x = -1 and x = 3 are the solutions of the quadratic equation.
Step-by-step explanation:
x² - 2x = 3
Step 1. Convert to Standard Form by using Addition Property of Equality
x² - 2x = 3 to,
x² - 2x - 3 = 0
Step 2. Factor the Equation
x² - 2x - 3 = 0 to,
( x + 1 ) ( x - 3 ) = 0
Step 3. Get the two factors
( x + 1 ) ( x - 3 ) = 0 to,
x + 1 = 0 and x - 3 = 0
Step 4. Use Addition Property of Equality
x + 1 = 0 and x - 3 = 0 to,
x = -1 and x = 3
I hope it helps :)) kung no po ok sorry nlngg po manghuhula lng ehh..
Step-by-step explanation: